CD57+ EMRA CD8+ T cells in cancer patients over 70: associations with prior chemotherapy and response to anti-PD-1/PD-L1 therapy - Cécile Gonnin; Michelle Leemans; Florence Canoui-Poitrine; Morgane Lebraud; Aurélien Corneau; Louise Roquebert; Philippe Caillet; Pierre Gay; Johanna Canovas; Axelle Histe; Catherine Blanc; Carine El-Sissy; et al. (Immunity & Ageing, 2024)
Abstract Background Immune ageing complicates cancer treatment in older individuals. While immunotherapy targeting the PD-1/PD-L1 pathway can reinvigorate T cells, these cells tend to become senescent with age. This study investigates different CD8+ T cell subsets usually associated with senescence, in cancer patients over 70 years old who are undergoing anti-PD-1/PD-L1 immunotherapy, and examines the relationship between these senescent cells and prior chemotherapy exposure. We analyzed data from the Elderly Cancer Patient (ELCAPA) cohort, which included 35 patients enrolled between March 2018 and March 2021. Results Flow cytometry and unsupervised analysis were employed to characterize Effector Memory CD45RA+ (EMRA) and CD8+ T cell senescence at baseline, before initiating PD-1/PD-L1 therapy. EMRA cells were found to overexpress CD57 and KLRG1 compared to overall CD8+ T cells. Chemotherapy prior to anti-PD-1/PD-L1 was associated with an increased proportion of CD57+ EMRA CD8+ T cells (p = 0.009) and its granzyme B (GRZB) subset (p = 0.007). Using a 10% cut-off to define positivity, the six-month non-response tends to be associated with the CD57+ GRZB+ EMRA positivity (p = 0.097). Other CD8+ T cell subsets (EMRA, CD57+, or KLRG1+), usually associated with senescence, showed no significant association with previous chemotherapy or response to anti-PD-1/anti-PD-L1 therapy. Conclusions These findings underscore the impact of prior chemotherapy on expanding the pool of senescent T cells, particularly CD57+ EMRA CD8+ T and CD57+ GRZB+ EMRA CD8+ T cells, whose expansion could potentially affect the effectiveness of anti-PD-1/PD-L1 immunotherapy in elderly patients. This highlights the need for tailored approaches in this population.